Exploring the Relationship Between Coping Strategies and Resilience Among First-Year Kindergarten Children in Sapele, Delta State - Ekedama, Kate; Atubi, Onamrewho Favour (International Journal of Essential Competencies in Education, 2026)
This study examined the relationship between coping strategies and resilience among first-year kindergarten children in Sapele, Delta State. Specifically, it investigated the associations between problem-focused coping, emotion regulation coping, social support coping, and resilience during children’s early transition into formal schooling. A quantitative cross-sectional survey design was adopted. The study population comprised first-year kindergarten children enrolled in public and private schools in Sapele Local Government Area, Delta State. A stratified random sampling technique was used to select 316 children, ensuring proportional representation across school types. Data were collected using adapted measures of coping strategies and early childhood resilience. The instruments assessed problem-focused coping, emotion regulation coping, social support coping, and children’s academic, emotional, and social adaptation. Pearson Product-Moment Correlation was used to analyse the data at the .05 level of significance. The findings revealed a significant positive relationship between problem-focused coping and resilience, r = .263, p < .001, N = 316, indicating that children who engaged more actively in problem-solving tended to demonstrate higher resilience. However, emotion regulation coping was not significantly related to resilience, r = -.015, p = .793, N = 316, and social support coping also showed no significant relationship with resilience, r = -.026, p = .650, N = 316. These findings suggest that problem-focused coping may be a more visible coping resource among first-year kindergarten children, while emotion regulation and support-seeking behaviours may still be developing at this stage. The study highlights the need for early childhood classrooms to incorporate structured problem-solving activities and developmentally appropriate social-emotional learning experiences.